REFORMING THE ARMED FORCES OF THE COUNTRY AND MILITARY-PATRIOTIC EDUCATION AS A STRATEGIC ADVANTAGE IN THE ECONOMIC RIVALRY OF COUNTRIES IN THE GLOBAL ECONOMY (INNOVATIVE ECONOMY, 2020)
Honak I.M. REFORMING THE ARMED FORCES OF THE COUNTRY AND MILITARY-PATRIOTIC EDUCATION AS A STRATEGIC ADVANTAGE IN THE ECONOMIC RIVALRY OF COUNTRIES IN THE GLOBAL ECONOMYPurpose. The aim of the article is to study the features of mutual influence of expenditures of the Ukrainian state budget on national defence, youth and sports on the gross domestic product of Ukraine in the conditions of aggravation of economic rivalry in the global economy.Methodology of research. The following methods are used during the research: generalization of information and literature sources –  to formulate proposals on the progressive development of the Ukrainian economy and quality of its labour resources, on the cohesion of the society and its psychological and physical health through the implementation of expenditures of the Ukrainian state budget for national defence and youth and sports; regression and correlation analysis – to analyse the mutual impact of GDP and expenditures of the Ukrainian state budget on national defence, youth and sports.Findings. Methods for educating young people are proposed in order to provide an educated and physically healthy workforce for the national economy and defence and security. The influence of arms exports and military equipment on the economy of Ukraine is analysed. The need to carry out some reforms of the Armed Forces of Ukraine in order to increase the country's defence capability and ensure economic prosperity is substantiated. The correlation between the growth of gross domestic product and expenditures of the State Budget of Ukraine through the Ministry of Defence and the Ministry of Youth and Sports, which is linear, is established. Suggestions are made to reform other specific aspects of the state mechanism in order to increase the country's defence capability and ensure the following economic growth.Originality. The article provides suggestions for reforming youth policy and the national defence sphere to ensure economic growth and strengthen the country's defence capability.Correlation between the growth of gross domestic product and expenditures of the State Budget of Ukraine through the Ministry of Defence has been established (increase of expenditures on the Ministry of Defence by 1 billion hryvnias has a direct impact on GDP growth in the amount of 29.884 billion hryvnias) and the Ministry of Youth and Sports (growth spending on the Ministry of Youth and Sports by UAH 1 million influences GDP growth by UAH 1.045 billion), which is close.Practical value. The practical significance of the obtained results is the possibility of studying the mutual influence of the expenditures of the Ukrainian state budget, spent on national defence, youth and sports, on the gross domestic product of Ukraine in the conditions of aggravation of economic rivalry in the global economy.Key words: national security; arms and military equipment exports; military-patriotic education of youth; reform; economic growth; unemployment; employment; gross domestic product.
Keywords: Key words; national security; arms and military equipment exports; military-patriotic education of youth; reform; economic growth; unemployment; employment; gross domestic product.